Factors associated with institutional delivery in south Asian countries: evidence from five recent demographic and health surveys - Soni, Sifat Muntaha; Hossain, Md. Ismail; Akter, Salma; Ireen, Shahjadi; Sarkar, Shuvongkar; Parvin, Shahanaj; Begum, Mansura; Sultana, Rebeka (Research in Health Services & Regions, 2025)
Background Maternal and infant mortality is a major public health concern especially in South Asian nations. A significant proportion of mothers and infant died as a result of complications during birth. The delivery of healthcare facilities plays key role to lowering these mortality rates. The present study aimed to explore the prevalence of institutional delivery and its determinants in five South Asian countries. Methods Data were extracted from five South Asian countries latest demographic and health survey data, including Afghanistan (2015), Bangladesh (2017–18), Nepal (2016), Myanmar (2015–16), and Pakistan (2017–18), all of which were pooled for the present study. A total of 38,975 women were included in this study after data handling. A multivariate binary logistic regression model was performed to identify the factors influencing institutional delivery. Results More than half of all deliveries among the women were reported as occurring in a medical facility. The proportion of institutional deliveries was highest in Pakistan (68.80%), and lowest in Myanmar (40.60%). This study found that women who give birth at after 20 years’ age had 1.25 times higher chance of getting healthy facility during delivery (OR 1.25, [1.19, 1.32]). The odds of institutional delivery were 2.18 times higher for highly educated women (OR 2.18, [1.89, 2.52]) and 2.88 times higher for rich women (OR 2.88, [2.70, 3.07]). The likelihood of getting his wife delivered in a hospital increased with the husband’s education level. Women who accessed by any media showed 33% higher chance of getting healthy facility during child birth. Women who did not obtain ANC from a skilled provider had a reduced likelihood of selecting healthcare facility delivery by 71% (OR 0.29, [0.28, 0.31]) compared to women who did. Women who didn’t take any health care decision by-self had 16% lower chance of getting institutional delivery facility than others. Most importantly, rural area in south Asian countries presented lower odds of receiving healthy facility during delivery (OR 0.63, [0.59, 0.68]). Conclusions In conclusion, improving maternal health among South Asian countries requires addressing both individual and community-level factors. Women with higher education, better socioeconomic status, media exposure, and access to prenatal care are more likely to utilize medical services. Strengthening evidence-based health policies and ensuring strong leadership can enhance women’s quality of life through better access to health care.